Dehydration reduces stroke volume and cardiac output during exercise because of impaired cardiac filling and venous return, not left ventricular function. Issue 11 (15th June 2020) - Watanabe, Kazuhito; Stöhr, Eric J.; Akiyama, Koichi; Watanabe, Sumie; González‐Alonso, José
Abstract: Dehydration accrued during intense prolonged whole‐body exercise in the heat compromises peripheral blood flow and cardiac output ( Q ˙ ). A markedly reduced stroke volume (SV) is a key feature of the dehydration‐induced cardiovascular strain, but whether the lower output of the heart is mediated by peripheral or cardiac factors remains unknown. Therefore, we repeatedly quantified left ventricular (LV) volumes, LV mechanics (LV twist, a marker of systolic muscle function, and LV untwisting rate, an independent marker of LV muscle relaxation), left intra‐ventricular pressure gradients, blood volume and peripheral blood flow during 2 hr of cycling in the heat with and without dehydration (DEH: 4.0 ± 0.2% body mass loss and EUH: euhydration control, respectively) in eight participants (three females and five males). While brachial and carotid blood flow, blood volume, SV, LV end‐diastolic volume (LVEDV), cardiac filling time, systemic vascular conductance and Q ˙ were reduced in DEH compared to EUH after 2 hr, LV twist and untwisting rate tended to be higher ( p  = .09 and .06, respectively) and intra‐ventricular pressure gradients were not different between the two conditions ( p  = .22). Furthermore, LVEDV in DEH correlated strongly with blood volume ( r  = .995, p  < .01), head and forearms beat volume ( r  = .98, p  < .05), and diastolic LV filling time ( r  = .98, p  < .05). These findings suggest that the decline in SV underpinning the blunted Q ˙ with exercise‐induced dehydration is caused by compromised LV filling and venous return, but not intrinsic systolic or diastolic LV function. Abstract : Dehydration reduces stroke volume and cardiac output during intense prolonged exercise in the heat, but the underlying peripheral and cardiac mechanisms are not fully understood. We show that the reduced stroke volume accounting for the impaired cardiac output is closely associated with diminished left ventricular filling secondary to decreased peripheral blood flow and volume, compromised venous return, and reduced cardiac filling time. These findings highlight the importance of peripheral mechanisms in cardiac performance during exercise.